Navigating Campus Traffic: Analysing the Impact of Land Use on Congestion at King Abdulaziz University, Jeddah, Saudi Arabia - Apri Zulmi Hardi; Jamal Abdulmohsen Eid Abdulaal (Journal of Applied Geospatial Information, 2025)
The present research examines the correlation between land use and traffic congestion at King Abdulaziz University in Jeddah, Saudi Arabia. The authors analyze the Congestion Index Value (CIV) data and land use proportions to determine the main factors that contribute to congestion. Additionally, the authors examine how different land use arrangements affect traffic flow on the campus. The analysis employs both Ordinary Least Squares (OLS) and Geographically Weighted Regression (GWR) models to consider spatial variability. The findings demonstrate that specific purposes, such as hospitals, housing, areas designated for females, and central administrative structures, have a substantial impact on traffic flow. Furthermore, the presence of educational structures and their closeness to different entrances on campus are crucial determinants of congestion levels. The research indicates that strategically locating facilities and optimizing infrastructure near important entrances can reduce congestion and improve movement on campus. These insights offer essential direction to urban planners and university administrators in formulating efficient traffic management and sustainable urban development policies.